OBESITAS SENTRAL BERHUBUNGAN DENGAN TOLERANSI GLUKOSA TERGANGGU PADA MURID PEREMPUAN BEBERAPA SEKOLAH SWASTA DI YOGYAKARTA - , LUCIA MAWARTI DWI ASTUTI; , dr. Endy Paryanto P, MPH, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Background: Obesity in adolescents has become health problem. Central obesity is associated with insulin resistance. Theoretically, insulin resistance will cause impaired glucose tolerance (IGT), and it could develop into type 2 diabetes. The aims of this study are to evaluate the difference in IGT prevalence in central and non central obesity and to identify the risk factors associated with IGT. Methods: We conducted a cross sectional study at 3 private secondary schools in Yogyakarta, and recruited 62 obese female students aged 12-18 years. We classified the subjects into central obesity (BMI > +2SD and waist circumference > p90) and non central obesity based on anthropometric. Fasting glucose and 2 hours after loading were measured in all subjects. Differences in proportions between the two groups was calculated using chi-square test and risk factors associated with IGT were calculated using multivariate logistic regression with 95% confidence interval. Results: Out of 62 subjects, 14 subjects revealed IGT and central obesity showed significantly higher prevalence compared to non central obesity (11/31 vs 3/31 , P = 0.03). We also found that central obesity is the only risk factor of IGT (OR = 4.6